2004
DOI: 10.1046/j.1398-9995.2003.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Monosodium benzoate hypersensitivity in subjects with persistent rhinitis

Abstract: Background:  Very few data are available from the literature on whether nonatopic subjects affected by persistent rhinitis may show the appearance of objective symptoms of rhinitis after the ingestion of food additives such as tartrazine (E102), erythrosine (E127), monosodium benzoate (E211), p‐hydroxybenzoate (E218), sodium metabisulphite (E223), and monosodium glutamate (E620). It is still unclear whether the ingestion of food additive may cause, as well, a consensual reduction of nasal peak inspiratory flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Hypersensitivity to food additives, such as preservatives and colouring agents, may also induce symptoms of rhinitis [31]. However, these agents may partly be trigger factors rather than aetiological factors [32].…”
Section: Discussionmentioning
confidence: 99%
“…Hypersensitivity to food additives, such as preservatives and colouring agents, may also induce symptoms of rhinitis [31]. However, these agents may partly be trigger factors rather than aetiological factors [32].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the following tests were performed: skin prick test for common aeroallergens and food allergens 26 ; hematologic parameter assessment (hemoglobin, red blood cell, platelet, and white blood cell counts); biochemical assessment (serum electrolytes [sodium and potassium]); indices of renal function (creatinine, urea, and urine analysis) and hepatic function (alkaline phosphatase, aspartate aminotransferase, alanine aminotransferase, and g-glutamil-transpeptidase); glucose-fasting testing; and C-reactive protein, serum total IgE, and antinuclear and antithyroid antibody measurement. Finally, in all patients we performed an intradermal test with autologous serum 2 and double-blind placebo-controlled challenges with ASA, NSAIDs, and food additives, as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, in all patients we performed an intradermal test with autologous serum 2 and double-blind placebo-controlled challenges with ASA, NSAIDs, and food additives, as previously described. 19,26,27 Efficacy assessments…”
Section: Methodsmentioning
confidence: 99%
“…Some studies suggested that very high intake of benzoic acid can cause adverse health effects such as metabolic acidosis, hyperpnoea and convulsions (1). Few epidemiologic studies reported allergic reactions to benzoic acid and benzoate (urticaria, rinhitis and pruritis) (3)(4)(5). For this reason, estimation of daily intake of these additives is of public health concern.…”
Section: Introductionmentioning
confidence: 99%